APOLOGIZING STRATEGIES REALIZATION OF INDONESIAN: A CASE STUDY OF THE UNIVERSITY OF KUNINGAN STUDENTS - Ayang Winda SW (English Review: Journal of English Education, 2014)
Abstract: This study examines the apologizing strategies used by 20 Indonesian students of the Kuningan University. A 8-item Discourse Completion Task and interview are used to collect the data to know the apologizing strategies and the dominant strategies they used. This research applied the apologizing speech act of Indonesian in apologizing which is analyzed by using Blum-Kulka (1984). The findings show that there are various strategies used by then when apologizing. That strategies including IFID, addressed, an explanation or account of situation, acknowledgement of responsibility, offer of repair and promise forbearance, phatic and interjection. IFID was used by them as a favorite strategy. Generally, they used different ways when apology depend on power, social distance and ranking of imposition. Keywords: apology, strategy, Indonesian students